The Effect of Confidence in Valuation Estimates on Arbitrager Behavior and Market Prices. Issue 3 (3rd July 2018) - Murphy, Austin; Fu, Liang
ABSTRACT: The authors develop a complete framework for optimizing trading decisions that incorporates investors' confidence in their valuation estimates. Quantified estimates of arbitragers' uncertainty about their appraisals of asset values are shown to be extractable from market prices alone. An empirical investigation over the 1977–2015 interval indicated that confidence levels exhibit persistence subject to mean reversion, with a positive relationship found with the magnitude of existing mispricings. Higher returns are discovered to long (short) arbitrage of an asset, whose intrinsic value is higher (lower) than the market price, after rises in uncertainty among informed investors.